Plantas que atraen aves: Ibapoy - Haene, Eduardo; Gil, Guillermo; Di Giacomo, Alejandro (Revista Aves Argentinas, 2010)
Accedé al artículo ingresando a la revista (hacé click sobre la portada y/o el número).